The conserved Arg241‐Glu439 salt bridge determines flexibility of the inositol 1, 4, 5‐trisphosphate receptor binding core in the ligand‐free state. Issue 10 (23rd July 2013) - Ida, Yoichi; Kidera, Akinori
ABSTRACT Inositol 1, 4, 5‐trisphosphate receptor (InsP3R) is an intracellular Ca2+‐release channel activated by binding of inositol 1, 4, 5‐trisphosphate (InsP3) to the InsP3 binding core (IBC). Structural change in the IBC upon InsP3 binding is the key process in channel pore opening. In this study, we performed molecular dynamics (MD) simulations of the InsP3‐free form of the IBC, starting with removal of InsP3 from the InsP3‐bound crystal structure, and obtained the structural ensemble of the InsP3‐free form of the IBC. The simulation revealed that the two domains of the IBC largely fluctuate around the average structure with the hinge angle opened 17° more than in the InsP3‐bound form, and the twist angle rotated by 45°, forming interdomain contacts that are different from those in the bound form. The InsP3 binding loop was disordered. The InsP3‐free form thus obtained was reproduced four times in simulations started from a fully extended configuration of the two domains. Simulations beginning with the fully extended form indicated that formation of a salt bridge between Arg241 and Glu439 is crucial for stabilizing the closed form of the two domains. Mutation of Arg241 to Gln prevented formation of the compact structure by the two domains, but the fully flexible domain arrangement was maintained. Thus, the Arg241‐Glu439 salt bridge determines the flexibility of the InsP3‐free form of the IBC.Proteins 2013; 81:1699–1708. © 2013 Wiley Periodicals, Inc.